Papel del resveratrol en la modulación de la respuesta inflamatoria y antioxidante microglial en un modelo de encefalopatía del prematuro - Stern, Aníbal (2021)
Preterm birth is one of the leading causes of perinatal morbidity and mortality worldwide. Premature newborns have a high predisposition to the develop complications that negatively affect the development of their central nervous system (CNS). This set of impairments of both the gray and white matter in the premature newborn are globally known under the name of encephalopathy of prematurity. It is estimated that each year, perinatal lesions are responsible for more than one million new cases of neonatal encephalopathy and almost half a million infants with disabilities such as cerebral palsy. Numerous studies suggest the existence of a strong association between maternal infections, inflammation and perinatal brain damage, leading subsequently to neurological disability. The mechanisms by which maternal infections endanger fetal development are not fully understood. However, several reports point to the excessive production of proinflammatory mediators, chemokines and reactive oxygen and nitrogen species in the CNS as a result of an excessive microglial activation. Therefore, the search for molecular targets that allow the modulation of microglial reactivity represents a promising therapeutic strategy. In this way, resveratrol, a stilbene present in various red fruits, peanuts and red wine, is pointed as a potential candidate. Several studies have demonstrated the neuroprotective effects of resveratrol over experimental models of adult CNS injury, both in vivo and in vitro. In this project, we decided to investigate whether resveratrol protects the fetal CNS by modulating the microglial response in a model of encephalopathy of prematurity.